Редкие птицы Восточного Приазовья - Очаповский, В.С. (Вестник зоологии, 1971)
As a result of investigations for many years it was established that some species of birds of the eastern Azov sea territory that were considered previously to be very rare are not such in reality. The species of birds really rare for the eastern Azov sea territory are given in the article.